Lipid-lowering drugs affect lung cancer risk via sphingolipid metabolism: a drug-target Mendelian randomization study - Li, Honglin; Zhang, Lei; Yang, Feiran; Feng, Xiaoteng; Fu, Rong; Zhao, Ruohan; Li, Xiurong; Li, Huijie (Frontiers in Genetics, 2023)
The causal relationship between lipid-lowering drugs (LLD) use and lung cancer risk is controversial, and the role of sphingolipid metabolism in this effect remains unclear.Methods: Genome-wide association study data on low-density lipoprotein (LDL), apolipoprotein B (ApoB), and triglyceride (TG) were used to develop genetic instrumental variables (IVs) for LLD.2 Two-step Mendelian randomization analyses were performed to examine the causal relationship between LLD and lung cancer risk. The effects of ceramide, sphingosine-1-phosphate (S1P), and ceramidases on lung cancer risk were explored, and proportions of the effects of LLD on lung cancer risk mediated by sphingolipid metabolism were calculated.: APOB inhibition decreased the lung cancer risk in ever-smokers via ApoB (odds ratio [OR] 0.81 [95% confidence interval [CI] 0.70-0.92], P = 0.010), LDL (0.82 [0.71-0.96], P = 0.040), and TG (0.63 [0.46-0.83], P = 0.015) reduction by 1 standard deviation (SD), and decreased small cell lung cancer (SCLC) risk via LDL reduction by 1-SD (0.71 [0.56-0.90], P = 0.016), while decreased plasma ceramide level and increased neutral ceramidase level. APOC3 inhibition decreased the lung adenocarcinoma (LUAD) risk (0.60 [0.43-0.84], P = 0.039), but increased SCLC risk (2.18 [1.17-4.09], P = 0.029) via ApoB reduction by 1-SD. HMGCR inhibition increased SCLC risk via ApoB reduction by 1-SD (3.04 [1.38-6.70], P = 0.014). LPL agonist decreased SCLC risk via ApoB (0.20 [0.07-0.58], P = 0.012) and TG reduction (0.58 [0.43-0.77], P = 0.003), while increased plasma S1P level. PCSK9 inhibition decreased ceramide level. Neutral ceramidase mediated 8.1% and 9.5% of the reduced lung cancer risk in ever-smokers via ApoB and TG reduction by APOB inhibition, respectively, and mediated 8.7% of the reduced LUAD risk via ApoB reduction by APOC3 inhibition.We elucidated the intricate interplay between LLD, sphingolipid metabolites, and lung cancer risk. Associations of APOB, APOC3, HMGCR inhibition, and LPL agonist with distinct lung cancer risks underscore the multifaceted nature of these relationships. The observed mediation effects highlight the considerable influence of neutral ceramidase in the lung cancer risk reduction achieved by APOB and APOC3 inhibition.